Implementasi Basis Data sebagai Langkah Inovatif untuk Pengarsipan Dokumen di Rukun Tetangga - Almansyah, Muhamad Fadly; Dwi Kurniawan, Dwi Kurniawan (Applied Information Technology and Computer Science (AICOMS), 2024)
Digitalization is one of the most influential technological advancements today, including in document or archive management. Physical archives are often vulnerable to damage and challenging to access, making digitalization a solution to enhance accessibility, storage efficiency, and archive protection. This study aims to implement a document database in the neighborhood association environment (rukun tetangga) as an innovative step toward digital archiving. The methodology used is the waterfall development model, which includes the stages of requirements analysis, system design, database implementation, and performance evaluation. The results of the study indicate that implementing a database for document archiving at the neighborhood association level successfully improves the quality of administrative services, supports transparency, and strengthens the accountability of local document management. This study contributes a simple database that facilitates archive digitalization in neighborhood associations, which can be further developed for broader applications in the future.